1983
DOI: 10.1111/j.1365-2842.1983.tb01470.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of the distribution of occlusal tooth contacts in the intercuspal position at light and hard pressure in adults

Abstract: Young adults (Md 24) and Adults (Md 41) were examined with respect to the distribution of occlusal contacts in molars, premolars and anterior teeth when exerting light and hard pressure respectively in the habitual intercuspal position. There was no difference between the right and left side and the number of contacts per tooth was low. In all groups of teeth there was a smaller number of contacts at light pressure. The lower number of contacts at light pressure in Adults when comparing with Young adults was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
28
3
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 13 publications
9
28
3
2
Order By: Relevance
“…The results of the present study showed that the occlusal contact area increased with clenching intensity, which is in accord with the previous finding (Riise and Ericsson, 1983), and further clarified that the occlusal contact area increased in parallel with the bite force. The increase in contact area would give rise to a fairly constant average bite pressure.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study showed that the occlusal contact area increased with clenching intensity, which is in accord with the previous finding (Riise and Ericsson, 1983), and further clarified that the occlusal contact area increased in parallel with the bite force. The increase in contact area would give rise to a fairly constant average bite pressure.…”
Section: Discussionsupporting
confidence: 94%
“…This finding was in agreement with that of earlier investigators (Riise, 1982;Riise & Ericsson, 1983) who analysed occlusal contacts in the intercuspal position at light and hard pressure in adults. This suggests that occlusal instability seems to be a common condition, often stated clinically as light pressure by contacts only on one side, or lack of contacts on the molar teeth, which in both cases produce pivot effects on the mandible (Riise, 1982).…”
Section: Discussionsupporting
confidence: 94%
“…33,34 The mean bite force in patients with OSA after OA therapy had been shown to be around 400 N, 25 the load selected for this study. Therefore, it is considered that most of the relevant OCs were identified and recorded.…”
Section: Discussionmentioning
confidence: 99%